2016
DOI: 10.1016/j.biomaterials.2015.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-film enhanced chitosan nerve guides for long-distance regeneration of peripheral nerves

Abstract: Biosynthetic nerve grafts are developed in order to complement or replace autologous nerve grafts for peripheral nerve reconstruction. Artificial nerve guides currently approved for clinical use are not widely applied in reconstructive surgery as they still have limitations especially when it comes to critical distance repair. Here we report a comprehensive analysis of fine-tuned chitosan nerve guides (CNGs) enhanced by introduction of a longitudinal chitosan film to reconstruct critical length 15 mm sciatic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
161
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 166 publications
(183 citation statements)
references
References 37 publications
20
161
0
2
Order By: Relevance
“…Series of 40 blind‐coded cross‐sections (7 μm) were prepared. Hematoxylin and eosin staining (HE) was applied to selected sections and consecutive sections were double stained for neurofilament (NF200) (Meyer et al., 2016) and myelin basic protein (MBP). Briefly, sections were incubated in blocking solution (3% milk powder (Bio Magermilch Pulver, Heirler Cenovis GmbH, Germany) and 0.5% triton X‐100 (Roche Diagnostics GmbH, Germany) in PBS) prior to incubation with the following antibodies one after the other: (i) primary rabbit α‐NF200 antibody (against phosphorylated NFeH, N4142, 1:500, Sigma‐Aldrich GmbH, Germany, RRID:AB_477272, +4°C overnight), (ii) Alexa 488‐conjugated secondary goat α‐rabbit antibody (A11034, 1:1,000, Invitrogen AG, Germany, 1 hr at room temperature (RT)), (iii) mouse α‐MBP antibody (SMI94, 1:200, Covance Antibody Products, Germany, RRID:AB_510039, +4°C overnight), and (iv) Alexa 555‐conjugated secondary goat α‐mouse antibody (A21422, 1:1,000, Invitrogen AG, 1 hr at RT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Series of 40 blind‐coded cross‐sections (7 μm) were prepared. Hematoxylin and eosin staining (HE) was applied to selected sections and consecutive sections were double stained for neurofilament (NF200) (Meyer et al., 2016) and myelin basic protein (MBP). Briefly, sections were incubated in blocking solution (3% milk powder (Bio Magermilch Pulver, Heirler Cenovis GmbH, Germany) and 0.5% triton X‐100 (Roche Diagnostics GmbH, Germany) in PBS) prior to incubation with the following antibodies one after the other: (i) primary rabbit α‐NF200 antibody (against phosphorylated NFeH, N4142, 1:500, Sigma‐Aldrich GmbH, Germany, RRID:AB_477272, +4°C overnight), (ii) Alexa 488‐conjugated secondary goat α‐rabbit antibody (A11034, 1:1,000, Invitrogen AG, Germany, 1 hr at room temperature (RT)), (iii) mouse α‐MBP antibody (SMI94, 1:200, Covance Antibody Products, Germany, RRID:AB_510039, +4°C overnight), and (iv) Alexa 555‐conjugated secondary goat α‐mouse antibody (A21422, 1:1,000, Invitrogen AG, 1 hr at RT).…”
Section: Methodsmentioning
confidence: 99%
“…Usage of ANGs, however, leads to considerable donor side morbidity. Therefore, autologous muscle‐in‐vein grafts (MVGs), leading only to minor donor side morbidity (Manoli, Schulz, Stahl, Jaminet, & Schaller, 2014), represent promising alternative digital nerve grafts (Manoli, Schulz, et al., 2014; Marcoccio & Vigasio, 2010; Tos, Battiston, Ciclamini, Geuna, & Artiaco, 2012) as do several clinically approved biodegradable nerve guidance conduits (NGCs) (Bertleff, Meek, & Nicolai, 2005; Donoghoe, Rosson, & Dellon, 2007; Lohmeyer, Siemers, Machens, & Mailander, 2009; Meyer et al., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In these cases, in order to limit morbidity, reconstruction by direct nerve repair with epineurial microsutures or nervous grafts may be performed. In addition to these procedures, there are novel and upcoming techniques using biocompatible scaffolds that may help in the reconstruction of the transected nerve (32)(33)(34)(35)(36).…”
Section: Imaging and Diagnosismentioning
confidence: 99%
“…In vitro, it has been shown that chitosan membranes are a suitable substrate for survival and orientation of Schwann cell growth as well as survival and differentiation of neuronal cells [31,32]. In vivo, studies showed that chitosan tubes can efficiently bridge peripheral nerve defects [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%